Factors Influencing Student’s Intention to be An Entrepreneur (Literature Study) - Amrullah, Andi; Wahyudi, Sigit; Hapsari, Maulani Mega (Proceedings International Conference on Education Innovation and Social Science, 2022)
Indonesia's workforce continues to experience a decline in productivity, poor management skills, and an inability to respond to world challenges and competition. Therefore, comprehensive preparation is needed through humandevelopment and community initiatives. Based on the highest education completed by the labor force, the OpenUnemployment Rate (Tingkat Pengangguran Terbuka/TPT) in February 2022 has almost the same pattern as February 2021. In February 2022, the TPT from vocational high school (SMK) graduates was still the highest compared to graduates of other levels of education. The semi-systematic or narrative literature review approach is designed for topics that have been conceptualized differently and studied by different groups of researchers in different disciplines and that hinder the process of full systematic review. Given that situation at all levels of student’s environment encourage schools to embed an enterprising entrepreneurial skill into the national educational system, and together with the high desirability from students. There are at least four major factors that influencing student to be an entrepreneur; Family conditions have a significant influence on student entrepreneur interest. The family environment, in which the majority of the members are entrepreneurs, will serve as an example for the students; Entrepreneurship education and school environment has a positive impact on students' entrepreneurial ambitions and mindset; Personality on student independence for entrepreneurship, personality has a beneficial impact on student independence for entrepreneurship; Gender, a modest impact of entrepreneurship education on entrepreneurial intention with gender as a moderating element; schools must present all male and female student activities.